Respuestas

¡La mejor respuesta!
2012-12-01T16:57:53+01:00

P(x) = 3x³ - 2x² + 7     Q(x) = 4x² + 3x - 2


a)P(x) + Q(x) =  3x³ - 2x² + 7 + 4x² + 3x - 2 = 3x³ - 2x² + 4x² + 3x - 2 + 7 = 

                    = 3x³ +2x² + 3x + 5 


b)P(x) - Q(x) =  3x³ - 2x² + 7 - (4x² + 3x - 2) = 3x³ - 2x² + 7 - 4x² - 3x + 2 = 

                   = 3x³ - 2x² + 7 - 4x² - 3x + 2 = 3x³ - 2x² - 4x² - 3x + 2 + 7 = 

                   = 3x³ - 6x² - 3x + 9


c)Q(x) - P(x) = 4x² + 3x - 2 - (3x³ - 2x² + 7) = 4x² + 3x - 2 - 3x³ + 2x² - 7 = 

                   = - 3x³ + 4x² + 2x² + 3x - 2 - 7 = -3x³ + 6x² + 3x - 9


calificar como "mejor" solucion no cuesta nada.. saludos